PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KARTU SUKU KATA TERHADAP KETERAMPILAN MEMBACA PERMULAAN - Awalyah, Chusnul Chotimah; Arif, Khairan Muhammad (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
The purpose of this study was to find out influence of using syllable card learning media had on beginning reading skill. Ths research was conducted at Madrasah Ibitidaiyah Multazam rangkasbitung with a total sample of 12 respondents who were students of class I MI Multazam Rangkasbitung. Research subject was consisted of an experimental class and a control class. This research is a quantitative research with a quasi experimental method. Dtaa collecting techniques used in this study are interview and test. The test used in this study is areading skill’s test using a pretest and posttest. The data analysistechniques used in this study included homogenity test, normality test and hypothesis testing. Based on the result of the paired sample t test, output of the T test resulted obtained sig .000. which means <0.05, thus Ho is rejected and Ha is accepted. So it can be concluded that there is a significant effect of using syllable card learning media on the initial reading skills Keywords: Skill, Reading, Media, Syllable Card